2015
DOI: 10.1111/psyp.12589
|View full text |Cite
|
Sign up to set email alerts
|

Pay attention to me! Late ERPs reveal gender differences in attention allocated to romantic partners

Abstract: The present study employed late ERPs to examine differences in the association between neural responses to romantic partners and relationship quality factors across men and women. Participants passively viewed photos of their romantic partners, celebrities, and strangers during a computerized facial processing task. All participants demonstrated enhanced positivity to partner faces at late ERP components (P3 and LPP), furthering the notion that significant others elicit more motivated and sustained attention t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 55 publications
1
12
0
Order By: Relevance
“…For example, neutral images containing people elicit a larger LPP compared to neutral images that do not contain people (Ferri, Weinberg, & Hajcak 2012). Further, even when considering the neural response to people, the LPP is potentiated to faces of relatives (Grasso & Simons, 2011), faces of romantic partners (Burdwood & Simons, 2016), as well as one's own name and face (Tacikowski & Nowicka, 2010). Bradley's (2009) operationalization of significance in terms of activation of motivational systems provides a framework for understanding this variability in the LPP across stimulus types.…”
Section: Seminal Studiesmentioning
confidence: 99%
“…For example, neutral images containing people elicit a larger LPP compared to neutral images that do not contain people (Ferri, Weinberg, & Hajcak 2012). Further, even when considering the neural response to people, the LPP is potentiated to faces of relatives (Grasso & Simons, 2011), faces of romantic partners (Burdwood & Simons, 2016), as well as one's own name and face (Tacikowski & Nowicka, 2010). Bradley's (2009) operationalization of significance in terms of activation of motivational systems provides a framework for understanding this variability in the LPP across stimulus types.…”
Section: Seminal Studiesmentioning
confidence: 99%
“…Even though the LPP is larger for stimuli that are attended, it has also been shown that the LPP is larger for emotional than neutral stimuli under passive viewing conditions (Schupp et al, 2007), which corresponds with the notion that emotional information is preferentially processed even when it is task-irrelevant (Compton, 2003). Several studies have shown that the LPP is larger for pictures of the beloved compared to pictures of friends, celebrities, or strangers, when the pictures are taskrelevant, such as when participants are counting certain pictures or keeping track of who was depicted on the last picture (Burdwood and Simons, 2016;Langeslag et al, 2008;Langeslag et al, 2008Langeslag et al, , 2007. Other studies have shown that the LPP is enhanced for beloved-related pictures and words compared to information that is related to friends, parents, babies, or strangers under passive viewing conditions as well (Guerra et al, 2011;Langeslag et al, 2015;Langeslag and Van Strien, 2016).…”
Section: Introductionmentioning
confidence: 59%
“…The ERP results have suggested that our attention is attracted more by familiar faces compared to unfamiliar ones due to emotional significance. For example, the faces of relatives, friends, and romantic partners induced greater positivity of ERPs over frontal to occipital midline areas than celebrities or strangers did [6][7][8]. Another study found a difference in ERPs between acquaintances' faces and newly-learned faces [5].…”
Section: Introductionmentioning
confidence: 98%
“…Many event-related potential (ERP) studies have investigated neural activity during face recognition in order to understand attentional processes related to the rapid processing of facial information [5][6][7][8][9]. The ERP results have suggested that our attention is attracted more by familiar faces compared to unfamiliar ones due to emotional significance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation